KEDUDUKAN SAUDARA DALAM KEWARISAN ISLAM DAN METODE HITUNGAN BAGIANNYA MENURUT KONSEP SYAJAROTUL MIRATS - Raja Ritonga; Amhar Maulana Harahap (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2023)
Islamic inheritance makes the line of blood relationship part of the cause of getting an inheritance. Therefore, kinship is a binding relationship for mutual inheritance. However, in practice a number of differences exist between siblings and half-siblings, between brothers and sisters. This study aims to describe the position of the siblings of the heir. Furthermore, this study also describes the method and practice of calculating the share of the brothers in Islamic inheritance according to the concept of syajarotul mirats. The research method used is a qualitative method with the type of library research. All required data is collected through searching a number of books, books, journals and other scientific works that are related to the research theme. Furthermore, the data were analyzed descriptively. The results of the study concluded that brothers in Islamic inheritance are grouped according to the strength of their kinship. The group of siblings is referred to as 'ayan, half-sisters are referred to as 'akhyaf and half-sisters seibu are referred to as 'allat. In the practice of determining the inheritance share, they are located as ashabul furudh, ashobah binnafsi, ashobah bilghoir and ashobah ma'alghoir.Keywords: Sibling Inheritance; A'yan; Akhyaf; 'Allat; Syajarotul Mirats.